2012
DOI: 10.1530/erc-12-0007
|View full text |Cite
|
Sign up to set email alerts
|

miR-200c is aberrantly expressed in leiomyomas in an ethnic-dependent manner and targets ZEBs, VEGFA, TIMP2, and FBLN5

Abstract: MicroRNA-200c (miR-200c) through repression of specific target genes has been associated with cellular transition, tumorigenesis, and tissue fibrosis. We explored the expression and functional aspects of miR-200c in genesis of leiomyomas (LYO), benign uterine tumors with fibrotic characteristic. Using LYO and matched myometrium (MYO; n=76) from untreated and from patients exposed to hormonal therapies (GNRH agonist (GNRHa), Depo-Provera, and oral contraceptives), we found that miR-200c was expressed at signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 68 publications
4
85
0
1
Order By: Relevance
“…Accumulated evidence suggests that microRNAs (miRNA), a member of non-protein coding small RNA, functions as key regulator of protein coding genes expression [28,29], and their deregulation or dysfunction has been associated with the inflammation, fibrosis and tumorigenesis [30,31]. Several miRNAs, including miR-29b [32], miR-93/106b [33], and miR-200c [34,35], are down-regulated in leiomyoma and involved in the development of uterus leiomyoma. In our study, we found that miR-197 was also down-regulated in human uterus leiomyomas in comparison with the adjacent normal uterus myometrium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated evidence suggests that microRNAs (miRNA), a member of non-protein coding small RNA, functions as key regulator of protein coding genes expression [28,29], and their deregulation or dysfunction has been associated with the inflammation, fibrosis and tumorigenesis [30,31]. Several miRNAs, including miR-29b [32], miR-93/106b [33], and miR-200c [34,35], are down-regulated in leiomyoma and involved in the development of uterus leiomyoma. In our study, we found that miR-197 was also down-regulated in human uterus leiomyomas in comparison with the adjacent normal uterus myometrium.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-93/106b directly and/or indirectly interacted with the 3 0 UTR of F3, IL8, CTGF, PAI-1 and play key roles in myometrium inflammation and tissue turnover [33]. MiR-200c interacted with the 3 0 UTR of IL-8 and targets a potential mediator of inflammation IKBKB in NF-kB signaling pathway [35], miR-200c also interacted with the 3 0 UTR of ZEBs, VEGFA, FBLN5, TIMP2 and promoted cellular transition, angiogenesis, and matrix remodeling [34].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several other miRNA direct targets have been characterized in leiomyoma. 82,83,84 More recently, Chuang et al 85 reported that miR-200c regulates IL8 expression by direct targeting IKBKB and alteration of NF-kB activity in leiomyoma.…”
Section: Dysregulation Of Mirna In Uterine Leiomyomamentioning
confidence: 99%
“…Subsequently, we performed a search in PubMed for these 14 miRNAs and found that 7 of them had been confirmed experimentally to target VEGFA, that is, miR-361 [40, 41], miR-140 [42], miR-15a [43], miR-15b [44], miR-205 [45], miR-206 [46], and miR-200c [47]. Therefore, we speculate that these miRNAs may target VEGFA and play a role in NSC behavior under hypoxia.…”
Section: Discussionmentioning
confidence: 99%